Causal association between cardiovascular diseases and erectile dysfunction, a Mendelian randomization study - Li, Qingying; Long, Qiang; Ren, Baoming; Bing, Sen (Frontiers in Cardiovascular Medicine, 2023)
Background Cardiovascular diseases (CVD), including coronary heart disease (CHD), heart failure, ischemic heart disease (IHD), and atrial fibrillation, are prevalent in the aged. However, the influence of CVD on ED is less investigated. This study was performed to clarify the causal association between CVD and ED. Materials and methods Genome-wide association studies (GWAS) datasets targeting CHD, heart failure, IHD, and atrial fibrillation were downloaded to retrieve single nucleotide polymorphisms (SNPs). Further, single-variable Mendelian randomization and multivariable Mendelian randomization (MVMR) were adopted to explore the causal association between CVD and ED. Results Genetically predicted CHD and heart failure were found to increase the risks of ED (OR = 1.09, P < 0.05 and OR = 1.36, P < 0.05, respectively). However, no causal association was disclosed among IHD, atrial fibrillation and ED (all P > 0.05). These findings remained consistent in sensitivity analyses. After controlling for body mass index, alcohol, low density lipoprotein, smoking and total cholesterol levels, the results of MVMR support the causal role of CHD on ED (P < 0.05). Similarly, the direct causal effect estimates of heart failure on ED were significant in MVMR analyses (P < 0.05). Conclusion Using genetic data, this study revealed that genetically predicted CHD and heart failure may predict better ED compared with atrial fibrillation and IHD. The results should be interpreted with caution and the insignificant causal inference of IHD still needs further verification in future studies.